THE SOCIOLINGUISTIC IMPACT OF NAMES IN BUILDING SELF-CONCEPT: A STUDY OF AGUATA CULTURAL GROUP IN ANAMBRA STATE (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2023)
This study examines Igbo names to ascertain the sociolinguistic and cultural impact of names in building self-concept among Aguata cultural group. Applying descriptive and survey approach, the researcher interviewed some selected parents in the area of study to know the reasons behind names given to their children and how they have affected their self-concept. Two theories were used for this study: the causal theory of names championed by Saul Kripke and the descriptive theory supported by Gareth Evans. The findings show that whereas some Igbo names are sentential, others are clausal and phrasal, thus revealing the innermost thoughts of the giver captured in apt language. More than mere labels or means of identification, names are seen to serve numerous purposes: theopheric identity, to identify religious inclinations of the bearer (and his/her parents), fate, hardships and history of parents (especially in child-bearing), social accomplishments of parents and special events that took place around the period of birth (temperonyms), and many other cultural and historic events that are captured in naming among Aguata people. It is recommended that parents and guardians should continue to give children names that are of great values because they have powers to ward off negative spiritual forces. Finally, traditional names and naming in Aguata is a priceless heritage which is done according to the thoughts, beliefs, experiences and philosophy which guard and guide the name- bearer to a successful life.
Keywords: anthroponomynames,onomastics,psychological and spiritual effects,self-concept